2022
DOI: 10.1155/2022/5009124
|View full text |Cite
|
Sign up to set email alerts
|

Selective Chelating Resin for Copper Removal and Recovery in Aqueous Acidic Solution Generated from Synthetic Copper-Citrate Complexes from Bioleaching of E-waste

Abstract: This research focused on batch experiment using a new generation of chelating resins via an ion exchange process to describe the metabolic adsorption and desorption capacity onto iminodiacetic acid/Chelex 100, bis-pyridylmethyl amine/Dowex m4195, and aminomethyl phosphonic/Lewatit TP260 functional groups in bioleaching. The results showed that Dowex m4195 had the highest performance of adsorption capacity for copper removal in both H+-form and Na+-form. Results for Lewatit TP260 and Chelex 100 revealed lower a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
11
0
1
Order By: Relevance
“…The peaks at 1715 and 1608 cm −1 , which appeared in the spectra after the ion exchange process (Cu(II)-loaded H + chelating resin Dowex-M4195), had been transformed into new broad absorption peaks. It indicated that those peaks may be attributed to the interactions/occurrence/combination [ 38 , 39 ] between nitrogen (protonated) and Cu(II) (divalent metal) [ 10 ]. In addition, the stretching vibration of the alkane groups (CH 3 , CH 2 and CH, 2 or 3 bands) was exhibited at around 2923 cm −1 and other fundamental peaks before and after the ion exchange process were almost the same.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks at 1715 and 1608 cm −1 , which appeared in the spectra after the ion exchange process (Cu(II)-loaded H + chelating resin Dowex-M4195), had been transformed into new broad absorption peaks. It indicated that those peaks may be attributed to the interactions/occurrence/combination [ 38 , 39 ] between nitrogen (protonated) and Cu(II) (divalent metal) [ 10 ]. In addition, the stretching vibration of the alkane groups (CH 3 , CH 2 and CH, 2 or 3 bands) was exhibited at around 2923 cm −1 and other fundamental peaks before and after the ion exchange process were almost the same.…”
Section: Resultsmentioning
confidence: 99%
“…These chelating resins were applied for extraction of various metals such as Pb(II)/lead, Cu(II)/copper, Cd(II)/cadmium, Zn(II)/zinc, La(III)/lanthanum, Ni(II)/nickel, Cr(III, IV)/chromium, Fe(II)/iron and Co(II)/cobalt ions [ 8 , 9 ] from aqueous solutions and especially in electronics waste applications at a low pH. As mentioned above, the literature reported that Dowex-M4195 chelating resin showed the best results in removing/ion exchange Cu(II) at a low pH of less than 2 [ 10 ] as compared to other functional groups of chelating resin. However, the selective chelating resins in terms of ionic form such as Na + and H + are still limited regarding information in the literature for removing of Cu(II) in the electronics industries.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the lack of selectivity of polymeric adsorbents has led to the development of new chelate polymers. In order to obtain a huge selectivity for metal ions (M X+ ) removal new chelate materials have been developed [ 1 , 2 ]. In this, natural and synthetic polymers have proven to be able in preconcentrating and separating M X+ [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the feasibility of different chemically modified polymers, namely chelating polymers, was tested in the field of wastewater treatment in search of more effective means of depollution. Furthermore, to improve their adsorption capacity, chemical modifications can be performed with chelating ligands that have the following functional groups in their structure: -COO -, -N=N-, -CO -, -SO 3 -, -NH 2 , -OH and -SH [9][10][11]. Thus, the recyclable aims including regeneration and reuse of chelating polymers are important attributes of green technologies.…”
Section: Introductionmentioning
confidence: 99%